Focal fluorine-18 fluorodeoxyglucose-avid parotid findings in patients with lung cancer: prevalence and characteristics. Issue 9 (September 2016) - Davidson, Tima; Komissar, Orna; Goshen, Elinor; Shalmon, Bruria; Chikman, Bar; Ben-Nun, Alon; Ben-Haim, Simona
Abstract : Objective: Correct interpretation of incidental tumors is important to plan an appropriate treatment. We assessed the incidence and imaging characteristics of fluorine-18 fluorodeoxyglucose ( 18 F-FDG)-avid focal parotid findings (FPFs) in patients with lung cancer. Patients and methods: FPFs in PET-computed tomography reports of cancer patients were searched. Those with known parotid malignancies, lymphoma, and diffuse 18 F-FDG uptake in the entire parotid gland were not included in the analysis. Results: FPFs were detected in 38/3120 cancer patients (1.23%), observed as a soft tissue mass with a mean diameter 1.6±0.5 cm (range 0.8–2.7 cm) and a mean maximum standardized uptake value of 7.7±3.7 (range 2.5–17.8). FPFs were observed in 23/604 (3.8%) patients with lung cancer, compared with 6/1366 (0.4%) with breast cancer and 5/842 (0.6%) with gastrointestinal malignancies. We assessed FPFs appearances in 23 patients with lung cancer (18 men, mean age 72.8±9.2); 20 (87%) were current or past smokers. There was no correlation between the stage or histopathological type of the lung cancer and the prevalence of parotid lesions. In four patients with histopathology, no malignancy was detected. For an additional 11 patients with available imaging and clinical follow-up (mean follow-up 15.5±13.5 months, range 3–42 months), FPFs were consistent with benign lesions. Conclusion: FPFs were more prevalent among patients with lung cancer than in patients with other malignancies. As 18 F-FDG avidity was moderate to high, FPFs may mimic distant metastases. It is important to consider FPFs in the interpretation of a focal parotid lesion as misinterpretation may result in denial of appropriate therapy.